Microbial cooperation in the rhizosphere improves liquorice growth under salt stress. Issue 4 (4th July 2017) - Egamberdieva, Dilfuza; Wirth, Stephan; Li, Li; Abd-Allah, Elsayed Fathi; Lindström, Kristina
ABSTRACT: Liquorice ( Glycyrrhiza uralensis Fisch.) is one of the most widely used plants in food production, and it can also be used as an herbal medicine or for reclamation of salt-affected soils. Under salt stress, inhibition of plant growth, nutrient acquisition and symbiotic interactions between the medicinal legume liquorice and rhizobia have been observed. We recently evaluated the interactions between rhizobia and root-colonizing Pseudomonas in liquorice grown in potting soil and observed increased plant biomass, nodule numbers and nitrogen content after combined inoculation compared to plants inoculated with Mesorhizobium alone. Several beneficial effects of microbes on plants have been reported; studies examining the interactions between symbiotic bacteria and root-colonizing Pseudomonas strains under natural saline soil conditions are important, especially in areas where a hindrance of nutrients and niches in the rhizosphere are high. Here, we summarize our recent observations regarding the combined application of rhizobia and Pseudomonas on the growth and nutrient uptake of liquorice as well as the salt stress tolerance mechanisms of liquorice by a mutualistic interaction with microbes. Our observations indicate that microbes living in the rhizosphere of liquorice can form a mutualistic association and coordinate their involvement in plant adaptations to stress tolerance. These results support the development of combined inoculants for improving plant growth and the symbiotic performance of legumes under hostile conditions.